2021
DOI: 10.21673/anadoluklin.736505
|View full text |Cite
|
Sign up to set email alerts
|

Bruksizm Varlığında ve Yokluğunda, Periodontal Sağlık ve Hastalıkta Vasküler Endotelyal Büyüme Faktörü, Hipoksi ile İndüklenebilir Faktör 1-Alfa ve Bakteriyel Plak Kompozisyonunun Değerlendirilmesi: Randomize Olmayan Klinik Çalışma

Abstract: In this study, we aimed to evaluate the possible changes in hypoxia markers and bacterial components in patients with periodontitis and bruxism. Methods: Four study groups were created: 20 healthy individuals without bruxism (Group 1), 20 periodontitis patients without bruxism (Group 2), 20 healthy individuals with bruxism (Group 3), and 20 periodontitis patients with bruxism (Group 4). Plaque index, gingival index, and clinical attachment levels were recorded and gingival crevicular fluid (GCF) and dental pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Although a former study of Akbulut. et al, [13] documented similar GCF lev els of VEGF in both healthy and diseased periodontal tissues, a study of Yılmaz et al, [14] revealed that smoking has decreased levels of VEGF in smoker patients with periodontitis.…”
Section: Disscussionmentioning
confidence: 93%
“…Although a former study of Akbulut. et al, [13] documented similar GCF lev els of VEGF in both healthy and diseased periodontal tissues, a study of Yılmaz et al, [14] revealed that smoking has decreased levels of VEGF in smoker patients with periodontitis.…”
Section: Disscussionmentioning
confidence: 93%